Lipids and Atherogenic Indices Fluctuation in Rheumatoid Arthritis Patients on Long-Term Tocilizumab Treatment - Fabio Cacciapaglia; Maria Grazia Anelli; Angela Rinaldi; Marco Fornaro; Giuseppe Lopalco; Crescenzio Scioscia; Giovanni Lapadula; Florenzo Iannone (Hindawi Limited, 2018)
Rheumatoid arthritis (RA) patients are at high risk of cardiovascular (CV) events, and the chronic inflammatory state may generate quantitative and qualitative changes in lipoprotein fractions. The anti-IL-6 receptor tocilizumab (TCZ), even if effective in inflammation and joint damage prevention, determined significant alterations to RA patients' lipid levels in randomized controlled trials, but real-world data are lacking. We evaluated the changes in lipid fraction levels and disease activity in a longitudinal cohort of RA patients on long-term treatment with tocilizumab (TCZ) in a community setting. We retrospectively selected 40 naïve-biologic RA patients on treatment with intravenous TCZ compared to 20 RA patients on methotrexate treatment as the control group. Total cholesterol (Tot-Chol), low-density lipoproteins (LDL), high-density lipoprotein (HDL), and triglyceride (TG) levels were measured at the baseline and at 12, 24, and 52 weeks thereafter. At the same points, 28-joint disease activity score (DAS28), clinical disease activity index (CDAI), and EULAR clinical responses were also assessed. During the first 24 weeks, we observed in TCZ-treated patients a progressive statistically significant (p<0.001) increase in Tot-Chol, LDL, HDL, and TG, which returned close to the baseline at 52 weeks. But no changes in the lipid-related CV risk indices Tot-Chol/HDL and LDL/HDL ratios and the atherogenic index (log10 TG/HDL) were detectable. Notably, we observed a statistically significant negative correlation between changes in lipid fractions and DAS28 or CDAI. The prolonged treatment with TCZ was associated to a transient increase in cholesterol's fractions during the first 6 months of treatment, with inverse correlation to disease activity, but with no impact on surrogate lipid indices of atherogenic risk. These findings may aid clinicians in interpreting the RA patient's lipid profile in daily clinical practice.